Guarding Public Coffers or Trapping the Poor? The Role of Public Assistance Asset Limits in Program Efficacy and Family Economic Well‐Being. Issue 1 (29th July 2019) - Hamilton, Leah; Rothwell, David; Huang, Jin; Nam, Yunju; Dollar, Taylor
Abstract : Devolution of the American welfare state over the last 40 years means that states have more control to set eligibility criteria in public assistance programs. One such criterion, limits on participant assets, is designed to improve program efficiency by allocating scarce public resources only to the truly needy, but it presents a unique set of barriers to financial independence for low‐income families. In this article, we present the historical policy context for asset limits in the primary cash assistance, food assistance, health, and disability programs in the United States and discuss the theoretical implications for program participation and efficiency, household assets, and the labor market. Finally, we provide a review of the existing empirical literature in each of these areas and recommendations for future research and policy development. Abstract : 过去40年间，美国这个福利国家的权力下放意味着各州在公共援助计划中有更多的控制权来设定合格标准。其中一个标准，即对参与者的资产限制，旨在通过只将稀缺的公共资源分配给真正需要帮助的人来提高计划效率。但它却为低收入家庭的经济独立设置了一道独特的屏障。本文介绍了美国主要现金援助、食品援助，以及健康和残疾计划中资产限额的历史政策背景，并探讨了其对计划参与和效率、家庭资产和劳动力市场的理论意义。最后，笔者回顾了这些领域现存的实证文献，并对今后的研究和政策制定提出了建议。 Abstract : La des evolución del estado de bienestar estadounidense en los últimos 40 años significa que los estados tienen más control para establecer los criterios de elegibilidad en los programas de asistencia pública. Uno de estos criterios, los límites de los activos de los participantes, está diseñado para mejorar la eficiencia del programa al asignar recursos públicos escasos solo a los verdaderamente necesitados, pero presenta un conjunto único de barreras a la independencia financiera para las familias de bajos ingresos. En este documento, presentamos el contexto histórico de políticas para los límites de activos en los programas de asistencia primaria en efectivo, asistencia alimentaria, salud y discapacidad en los Estados Unidos y discutimos las implicaciones teóricas para la participación y eficiencia de los programas, los activos de los hogares y el mercado laboral. Finalmente, proporcionamos una revisión de la literatura empírica existente en cada una de estas áreas y recomendaciones para futuras investigaciones y desarrollo de políticas.